2020
DOI: 10.3102/0162373720979177
|View full text |Cite
|
Sign up to set email alerts
|

Can Re-Enrollment Campaigns Help Dropouts Return to College? Evidence From Florida Community Colleges

Abstract: In this study, we develop and implement a text messaging re-enrollment campaign to encourage former community college students to return to college. Former students are randomly assigned to one of two treatment groups that either receives information to simplify the re-enrollment process or receives both information and a one-course tuition waiver. We find that providing information and a one-course tuition waiver to former students increases their likelihood of re-enrollment by 1.5 percentage points (21.1%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Moreover, digital media provide more flexibility to customize messages based on student data and responses.Our results also indicate that values-based interventions benefit students who have stopped out of college, not just those currently enrolled. Although most prior studies of text message interventions have targeted college-intending high school seniors or currently enrolled college students (e.g.,Castleman & Page, 2015O'Hara & Sparrow, 2019;Page & Gehlbach, 2017; seeOrtagus et al, 2021, for an exception), we found that our treatment increased reenrollment by 13 percentage points when students had stopped out prior, as opposed to only 4 percentage points when they had been recently enrolled. As community college enrollments have fallen almost 15% since the onset of the COVID-19 pandemic (National Student Clearinghouse, 2021), severely undercutting tuition revenue and keeping colleges understaffed, boosting enrollments back to pre-pandemic levels may be key to ensuring continued student success.…”
mentioning
confidence: 60%
“…Moreover, digital media provide more flexibility to customize messages based on student data and responses.Our results also indicate that values-based interventions benefit students who have stopped out of college, not just those currently enrolled. Although most prior studies of text message interventions have targeted college-intending high school seniors or currently enrolled college students (e.g.,Castleman & Page, 2015O'Hara & Sparrow, 2019;Page & Gehlbach, 2017; seeOrtagus et al, 2021, for an exception), we found that our treatment increased reenrollment by 13 percentage points when students had stopped out prior, as opposed to only 4 percentage points when they had been recently enrolled. As community college enrollments have fallen almost 15% since the onset of the COVID-19 pandemic (National Student Clearinghouse, 2021), severely undercutting tuition revenue and keeping colleges understaffed, boosting enrollments back to pre-pandemic levels may be key to ensuring continued student success.…”
mentioning
confidence: 60%
“…Community colleges provide critical developmental education for academically underprepared students (Bailey et al, 2015;Bemmel et al, 2008;Cohen & Brawer, 2008) and mobility pathways for working or low-income students (Armstrong & Hamilton, 2013). Although most community college students who leave college without a degree struggle with their entry-level coursework, a smaller share of noncompleters drop out after performing well in their introductory courses and making significant progress toward degree completion (Ortagus, Tanner, & McFarlin, 2020;Shapiro et al, 2019).…”
mentioning
confidence: 99%
“…To encourage these students to reenroll and complete their degree, many community colleges launch reenrollment campaigns targeted at former students who have already made considerable progress (Schwartz, 2019). While reenrollment campaigns can increase the 2 probability of former students returning to college (Ortagus, Tanner, & McFarlin, 2020), the likelihood of any student completing college after stopping out for a period of time is significantly lower when compared with students who remain enrolled (Crosta, 2014;DesJardins et al, 2006). 1 For community colleges facing limited resources and low completion rates, the most effective mechanism to optimize completion would be to prevent students from dropping out in the first place (e.g., Mabel & Britton, 2018).…”
mentioning
confidence: 99%